Analisis Pembelajaran Ekonomi Dalam Mencapai Profil Pelajar Pancasila Terhadap Pencapaian Karakter Siswa. - Yuli, Nor Yuli; Ratumbuysang, Monry Fraick Nicky Gillian; Nor, Baseran; Atmono, Dwi (Jurnal Pendidikan Ekonomi (JUPE), 2024)
This study aims to analyze economic learning in achieving the profile of Pancasila students towards the achievement of the character of public high school students in North Banjarmasin. The problem focused on the lack of independence of students learning economics students in developing the character of the research method used is descriptive research with a quantitative approach. Samples were taken using Purposive Random Sampling technique as many as 226 public high school students in North Banjarmasin. Data collection techniques through observation, interviews, documentation and questionnaires to students as well as taking references from journals, books and other relevant sources. Data analysis in this study was conducted using descriptive statistical analysis, classical assumption analysis, simple regression analysis and partial test (t-test). The results showed that there was a positive influence between economic learning in achieving the Pancasila student profile on the character assessment of public high school students in North Banjarmasin.